CLINICAL AND FUNCTIONAL CHARACTERISTICS OF JUVENILE RHEUMATOID ARTHRITIS DEBUT - A. K. Mikhaylova; Ye. Yu. Yemel'yanchik; A. B. Salmina; Ye. P. Kirillova; L. N. Antsiferova; I. Yu. Naumenko ("Paediatrician" Publishers LLC, 2011)
.